Communication - Morris, Ting; Nang Chan Yeema (New York, USA Ting Morris, 1995)
Describes means of communication from cave paintings to the information superhighway, and includes instructions on making craft projects such as code flags and a telegraph system.
Keywords: Adult Nonfiction